O teatro popular de Augusto Boal: do arena ao exílio - Nascimento, Caroline Araújo do [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
This paper has as a starting point the passage of Augusto Boal through the Teatro de Arena de São Paulo and his involvement in its artistic research development, with the aim of bringing a national identity to the Brazilian theater, which would dialogue with its people and integrates it into the scene. In the sequence, this research intends to understand the relevance of this process as a theoretical and practical basis so that Augusto Boal later would structure the Theater of the Oppressed techniques, pursuing the working class freedom and emancipation.

Este estudo tem como ponto de partida a passagem de Augusto Boal pelo Teatro de Arena de São Paulo e seu envolvimento no projeto de desenvolvimento da pesquisa artística do grupo, com objetivo de trazer uma identidade nacional para o teatro brasileiro que dialogasse com o povo e o integrasse ao fenômeno cênico. Na sequência, esta pesquisa se propõe a compreensão da relevância deste processo como base teórica e prática para que Augusto Boal posteriormente estruturasse as técnicas do Teatro do Oprimido, em busca da libertação e emancipação da classe trabalhadora.
Keywords: Boal, Augusto, 1931-2009; Teatro de arena; Teatro e sociedade